Iran and Serbia: difference that through dialogue turns into cooperation and friendship - Хасанпур, Рашид (Napredak, 2023)
Iran’s approach in the diplomatic relations with Serbia is long-lasting and of strategic character, based on the respect for mutual specifics, but also on firm understanding and need for even stronger cooperation. The long history of friendship has been shaped in the fires of large wars and crises for more than a century, with intensive diplomatic relations lasting for 85 years. The absence of unresolved problems in mutual relations indicates the quality of mutually proper cooperation, the priority of which is its deepening and directing from the sphere of politics to the fields of economy, science, education, culture and sport. The principled position in defending the attitudes of international politics and independence has further strengthened the friendship between the two countries.
Keywords: diplomatic relations; politics; economy; culture; Persia; Iran; Serbia; international law